2012
DOI: 10.2903/sp.efsa.2012.en-340
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between pesticides and other factors in effects on bees

Abstract: Bees are important pollinators of both managed crops and wild flora. An overview of the interactions between pesticides and other factors in effects on bees considered: 1) The importance of the different exposure routes in relation to the overall exposure of bees to pesticides; 2) Multiple exposure to pesticides (including substances used in bee medication) and potential additive and cumulative effects; and 3) Interactions between diseases and susceptibility of bees to pesticides. Nectar foraging bees are like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 229 publications
(262 reference statements)
0
34
0
3
Order By: Relevance
“…But, how does our exposure relate to the field? Nectar foragers are however more likely to experience the highest exposure to both sprayed and systemic seed and soil treatment compounds (Thompson 2012). Over the whole exposure period, our colonies consisted on average of 13,000 bees.…”
Section: Single Factor Imidaclopridmentioning
confidence: 99%
“…But, how does our exposure relate to the field? Nectar foragers are however more likely to experience the highest exposure to both sprayed and systemic seed and soil treatment compounds (Thompson 2012). Over the whole exposure period, our colonies consisted on average of 13,000 bees.…”
Section: Single Factor Imidaclopridmentioning
confidence: 99%
“…This is also true for honeybees (Thompson 2012;Johnson 2015). By far the majority of studies have reported synergistic interactions involving the inhibition of insecticide-metabolizing enzymes; such is the case of piperonyl butoxyde (PBO), one of the most commonly registered synergists used in plant protection formulations to enhance insecticide efficiency.…”
Section: Interaction Between Pesticidesmentioning
confidence: 99%
“…As an example, prochloraz, tebuconazole, flusilazole, and difenoconazole elevate the mortality rate of bees exposed to deltamethrin, alpha-cypermethrin, or lambda-cyhalothrin (Belzunces and Colin 1993;Pilling and Jepson 1993;Thompson and Wilkins 2003). In addition, the toxicity of the acaricides tau-fluvalinate and flumethrin (pyrethroid) can be enhanced by prochloraz and flusilazole, respectively (Thompson 2012). Data from Pilling et al (1995) indicates that the mechanism underlying these interactions is an inhibition of CYP450 activity by EBI fungicides, slowing detoxification of pyrethroid in bees.…”
Section: Interaction Between Pesticidesmentioning
confidence: 99%
“…Hives suffering from colony collapse have been shown to have a higher burden of viral, bacterial and fungal pathogens. Multiple studies indicate an increased toxic effect of certain pesticides in the presence of viral and fungal pathogens (Thompson 2012). It has also been suggested that prophylaxis of foulbrood disease with antimicrobials could upset the balance of gut flora in honeybees and negatively impact their health, as these bacteria aid digestion and detoxification (Tian et al 2012).…”
Section: Introductionmentioning
confidence: 99%